1987
DOI: 10.1139/v87-213
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gas-phase proton affinities of conjugate bases B's and free energies of hydration of conjugate acid ions BH+'s for B = alkyl-substituted H2O and NH3

Abstract: KENZO HIRAOKA. Can. J. Chem. 65, 1258 (1987. An approximate linear relationship between the proton affinities of conjugate bases (B 's) and the free energies of hydration of conjugate acid ions (BH' 's) is found for B = alkyl-substituted H 2 0 and NH3. With increase in proton affinities, the free energies of hydration increase linearly with a slope of about 1 for analogous compounds. The charge delocalization in the protonated bases and the structure-making effect induced by the hydrophobic groups in the alkyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Although other factors could be involved which determine where the ionizing protons reside (e.g. steric effects, charge solvation, and Coulombic effects), similar proton affinities between the N-terminal imidazole and the secondary ε-amino group suggest a fairly equal population of ions protonated at both sites [22,23]. We hypothesize, as illustrated in Scheme 1, that isomers protonated at the secondary ε-amino group can fragment via the CCE pathway through a charge-directed mechanism (eliminating [C 7 H 7 ] + ) while amide backbone fragmentation persists for isomers not protonated at that site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although other factors could be involved which determine where the ionizing protons reside (e.g. steric effects, charge solvation, and Coulombic effects), similar proton affinities between the N-terminal imidazole and the secondary ε-amino group suggest a fairly equal population of ions protonated at both sites [22,23]. We hypothesize, as illustrated in Scheme 1, that isomers protonated at the secondary ε-amino group can fragment via the CCE pathway through a charge-directed mechanism (eliminating [C 7 H 7 ] + ) while amide backbone fragmentation persists for isomers not protonated at that site.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that for simple peptides like the model GK-NHCH 3 , singly-charged precursors protonated at the secondary ε-amino group can fragment competitively either by the b n − y m or CCE pathways. However, another point to consider is that a secondary amino group typically has a higher gas-phase proton affinity [23] than primary amino groups. This implies that a greater distribution of ions could be protonated on the derivatized side chain compared to peptides containing unmodified lysyl residues and also suggests that more energy may be required to mobilize a proton from the secondary ε-amino group thus favoring the CCE pathway over the b n − y m pathway.…”
Section: Resultsmentioning
confidence: 99%
“…It is also reported that the proton transfer is less likely to occur between a weaker acid and a primary amine. 50,51 Moreover, the difference between the proton affinity of HAc (342.33 kcal mol −1 ) and ethanolamine (220.87 kcal mol −1 ) is large. The larger difference in proton affinities, the lower possibility of proton transfer between acid and base.…”
Section: Reports the Cosmo-rs Predictedmentioning
confidence: 99%
“…Similarly, the term microbasicity for polybasic molecules in solution can be defined. The basicity has been defined as a change in Gibbs free energy, Δ G , for protonation process, ${\rm{L}} + {\rm{H}}^ + \rightleftharpoons {\rm{HL}}^ +$ 13–15. Obviously, for a polybasic molecule when an individual site undergoes protonation, the related Δ G is a micro‐Δ G and corresponding basicity is a microbasicity for the molecule.…”
Section: Introductionmentioning
confidence: 99%